Higher Delta variant-specific neutralizing antibodies prevented infection in close contacts vaccinated with ancestral mRNA vaccines during the SARS-CoV-2 Delta wave - Goh, Yun Shan (2024)
Identification of the risk factors and the high-risk groups which are most vulnerable is critical in COVID-19 disease management at a population level. Evaluating the efficacy of vaccination against infections is necessary to determine booster vaccination strategies for better protection in high-risk groups. In this study, we recruited 158 mRNA-vaccinated individuals during the Delta wave of SARS-CoV-2 infections in Singapore and examined the antibody profiles of infected individuals. We found that, despite high exposure due to communal living conditions in proximity, 4% of individuals (6/158) had PCR-confirmed infections and 96% (152/158) remained uninfected. Time-course analysis of the antibody profile at the start and the end of quarantine period showed Delta-specific boosting of anti-spike antibody response in 57% of the uninfected individuals (86/152). In the remaining 43% of the uninfected individuals (66/152) with no Delta-specific antibody boost, we found a higher Delta-specific antibody response at the start of quarantine period, which correlated with higher Delta pseudovirus neutralizing capacity. Our findings indicate that a higher basal variant-specific antibody response in the mRNA-vaccinated individuals contributes to better protection against infections by the new emerging SARS-CoV-2 variants.